High Temperature Corrosion Behaviour Of Cold Rolled Additively Manufactured Stainless Steel 316L in Molten Solar Salt - Shankar, Gaurav (Cranfield University, 2025)
This thesis examines the high-temperature corrosion behaviour of cold-rolled additively manufactured stainless steel 316L (SS316L) in a molten solar salt environment, with a focus on its suitability for Concentrated Solar Power (CSP) thermal energy storage systems. SS316L samples were fabricated by Wire Arc Additive Manufacturing (WAAM), with some subjected to 120 kN cold rolling on each layer. These samples were exposed to a NaNO₃-KNO₃-KCl eutectic salt (molar ratio 10:78:12) at 607°C, under inert nitrogen, for up to 500 hours. Corrosion was assessed using mass change measurements, dimensional metrology, and detailed surface characterisation by SEM-EDS. The results showed that all samples initially gained mass, primarily due to oxide and salt deposition. Cold-rolled samples experienced significantly greater uniform metal loss (179 μm after 500 hours) compared to as-printed samples, indicating that grain refinement from rolling promotes more aggressive and uniform corrosion under prolonged exposure. SEM-EDS analysis revealed differences in corrosion mechanisms: cold-rolled specimens suffered from extensive salt infiltration and dissolution of surface oxides, while as-printed samples displayed thicker and more protective oxide scales but were more prone to localised corrosion and pitting. These findings indicate that microstructural modification by post-processing strongly influences corrosion response in molten salts, impacting material lifespan and system reliability for CSP. The results highlight key considerations for designing and selecting advanced steels for next-generation, high-temperature thermal storage environments.
Keywords: Concentrated solar power; Thermal Energy Storage; SEM; Cold rolling; WAAM (Wire Arc Additive Manufacturing); Corrosion